2018
DOI: 10.1002/jclp.22593
|View full text |Cite
|
Sign up to set email alerts
|

A reexamination of the cognitive behavioral model of chronic fatigue syndrome

Abstract: This model may not accurately represent the experience of individuals with CFS, particularly those who fulfill more stringent case definitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This has led to the predominant recommendation of CBT and GET as effective treatments. However, reviews by Song and Jason in 2005 [ 15 ] and Sunnquist and Jason in 2018 [ 16 ] showed that, if patients are selected who fulfil more stringent case definitions, so that ME/CFS patients are selected instead of those with a fatiguing psychiatric illness, then they do not possess the behavioural characteristics targeted by the CB model. Also, Geraghty et al [ 17 ] concluded that “the CBM [CB model] is not fit for purpose, as it poorly reflects the accounts given by patients and it ignores the wealth of evidence showing biological, immune and neurological dysfunction in ME/CFS”.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the predominant recommendation of CBT and GET as effective treatments. However, reviews by Song and Jason in 2005 [ 15 ] and Sunnquist and Jason in 2018 [ 16 ] showed that, if patients are selected who fulfil more stringent case definitions, so that ME/CFS patients are selected instead of those with a fatiguing psychiatric illness, then they do not possess the behavioural characteristics targeted by the CB model. Also, Geraghty et al [ 17 ] concluded that “the CBM [CB model] is not fit for purpose, as it poorly reflects the accounts given by patients and it ignores the wealth of evidence showing biological, immune and neurological dysfunction in ME/CFS”.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges to the CBM, in terms of efficacy and applicability, are scant in the literature and have not addressed the CBM in totality. Various studies have shown that patients do not possess some of the personality or behavioural characteristics deemed targets of treatment in the CBM (Song and Jason, 2005; Sunnquist and Jason, 2018). More recently, the model has come under scrutiny following publication of controversial clinical trials of CBT-GET, such as the PACE trial (Pacing, graded Activity, and Cognitive behaviour therapy: a randomised Evaluation) and the FINE trial (Fatigue Intervention by Nurses Evaluation) (Wearden et al, 2010; White et al, 2011) that sought to validate the CBM.…”
Section: Introductionmentioning
confidence: 99%
“…Davinton et al, 2004 ; Wessely et al, 1991 ). The methodology applied by Vercoulen et al (1998) was subsequently criticized, because the model could not be replicated for people fulfilling the ME/CFS case definitions ( Sunnquist and Jason, 2018 ), and CBT and GET have been shown to have null effects or even aggravate ME/CFS symptoms (e.g. Kindlon, 2017 ; Wilshire et al, 2018 ).…”
Section: The Role Of Causal Attributions For Stigma In Me/cfsmentioning
confidence: 99%